Meningkatkan Kemandirian dan Hasil Belajar Materi Alat Ukur Tak Baku Untuk Siswa Kelas I SD Menggunakan Model Problem Based Learning - Elizabeth Daniar Ratih Nursanti; Ignatia Esti Sumarah (Jurnal THEOREMS (The Original Research of Mathematics), 2023)
This research was motivated by the low results of a study on documentation of Mid Semester Examination (UTS) scores for learning mathematics and independence from 19 grade 1 students at SD N Bhaktikarya for the 2022/2023 academic year. Class average value of 70 (KKM Mathematics 75). This type of research is Classroom Action Research (CAR), which is carried out in 2 cycles, aims to improve mathematics learning outcomes on non-standard measuring instruments and independence by applying the model Problem Basesd Learning (PBL). Researchers used a test technique by analyzing the results of student worksheets (LKPD) on non-standard measuring instruments and guided by 8 indicators of independence in observing the increase in student independence. The percentage of classical mastery of students' mathematics learning outcomes before being given the action (pre-cycle) increased by 11% after being given the first action (cycle I) to 63% and increased after being given the second action (cycle II) to 79%. Application of models Problem Based Learning can increase the independence of students as seen from the percentage increase in pre-cycle by 34%, increased in cycle 1 by 55% and increased to 63% in cycle II. Based on the results of these studies, the application of the model PBL can improve learning outcomes and student independence.Keywords: classroom action research, problem based learning, learning outcomes, independence, non-standard measuring instrument teaching materials.